Post a New Question

math

posted by .

Factor each expression

(X+5)^3-(2x+1)^3

  • math -

    Using A^3 - b^3 = (A+B)(A^2 + AB + B^2)

    (x+5)^3-(2x+1)^3
    =( x+5 - 2x-1)( (x+5)^2 + (x+5)(2x+1) + (2x+1)^2 )
    = (4-x)(x^2 + 10x + 25 + 2x^2 + 11x + 5 + 4x^2 + 4x + 1)
    = (4-x)(7x^2 + 25x + 31)

    Here is a neat way to check our answer,
    let x be any value, say x = 1

    original value = 6^3 - 3^3 = 189
    factored form value = 3(63) = 189
    Even though this does not "prove" that my answer is correct, there is an extremely high probability that my answer is correct.

Answer This Question

First Name
School Subject
Your Answer

Related Questions

More Related Questions

Post a New Question